2014
DOI: 10.3109/09537104.2014.898178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pathogen reduction systems on platelet microRNAs, mRNAs, activation, and function

Abstract: Pathogen reduction (PR) systems for platelets, based on chemically induced cross-linking and inactivation of nucleic acids, potentially prevent transfusion transmission of infectious agents, but can increase clinically significant bleeding in some clinical studies. Here, we documented the effects of PR systems on microRNA and mRNA levels of platelets stored in the blood bank, and assessed their impact on platelet activation and function. Unlike platelets subjected to gamma irradiation or stored in additive sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 55 publications
3
75
0
1
Order By: Relevance
“…Therefore, it appears likely that pathogen reduction technologies may enhance the formation of platelet MPs in platelet concentrates. Although this hypothesis remains to be validated, preliminary data support it [57].…”
Section: Platelet Transfusionmentioning
confidence: 94%
See 2 more Smart Citations
“…Therefore, it appears likely that pathogen reduction technologies may enhance the formation of platelet MPs in platelet concentrates. Although this hypothesis remains to be validated, preliminary data support it [57].…”
Section: Platelet Transfusionmentioning
confidence: 94%
“…nucleases)/conditions of the extracellular milieu and contribute to the stability of microRNAs outside of cells. Platelets have been shown to release EVs upon activation by physiological agonists/mediators, such as (i) collagen, which mimics the matrix exposed upon damage of the vessel wall, (ii) ADP, which is released from activated platelets, and (iii) thrombin, which is generated during coagulation and is simulated by thrombinreceptor activating peptide (TRAP) [57]. Platelets are also activated by the increased shear stress caused by a reduced lumen at sites of atherosclerotic plaques.…”
Section: Platelets Release Extracellular Vesicles Upon Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this concept, recently, Osman et al [44] have reported changes in platelet miRNAs associated with different pathogen reduction treatments relative to respective controls, which further suggests that miRNAs of platelets have the potential to be the markers for a given context.…”
Section: Micrornas As Potential Platelet Markers Of Storage and Pathomentioning
confidence: 81%
“…Die möglichen Auswirkungen dieser Verfahren auf die Qualität und Wirksamkeit der Thrombozyten sowie im Hinblick auf mögliche Nebenwirkungen der Verfahren bzw. der dabei eingesetzten Stoffe werden wissenschaftlich noch diskutiert [178]. Der AK Blut stellte in seinen Ergän-zungen zum Votum 38 [179] …”
Section: Pathogeninaktivierungunclassified